2018
DOI: 10.1007/s10639-018-9758-7
|View full text |Cite
|
Sign up to set email alerts
|

A study into the usability and security implications of text and image based challenge questions in the context of online examination

Abstract: Online examinations are an integral component of online learning environments and research studies have identified academic dishonesty as a critical threat to the credibility of such examinations. Academic dishonesty exists in many forms. Collusion is seen as a major security threat, wherein a student invites a third party for help or to impersonate him or her in an online examination. This work aims to investigate the authentication of students using text-based and image-based challenge questions. The study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 26 publications
0
37
0
1
Order By: Relevance
“…3), memorability, usability, performance, and cost. Previous researches focus on the memorability and usability [16,17] that differs the Fig. 3 includes other collective techniques performance and cost.…”
Section: A Knowledge-based Authentication (Kba)mentioning
confidence: 99%
See 1 more Smart Citation
“…3), memorability, usability, performance, and cost. Previous researches focus on the memorability and usability [16,17] that differs the Fig. 3 includes other collective techniques performance and cost.…”
Section: A Knowledge-based Authentication (Kba)mentioning
confidence: 99%
“…According to the literature, KBA was identified as the approach used to combine some challenges (i.e. questions) to verify claimed users where the answers of these challenges came from their knowledge [16].…”
Section: Introductionmentioning
confidence: 99%
“…• A study [43] by authors identified that an increase in the number of questions shared, increased the success of an impersonation attack. Also, an increase in the profile (database) size decreased the success of an impersonation attack.…”
Section: Previous Researchmentioning
confidence: 99%
“…In another such episode, a renowned company Dunkin' Donuts faced a data breach on January 17, 2019, for another time in almost three months when hackers gained access to their customer's accounts through credential stuffing attacks [2]. On April 17, 2019 private data of about 100 million Just Dial end users was found undefended on openly available servers [3]. These reports of data breach are alarm bells that signal for prompt solutions and organizations cannot wait for more instances to happen.…”
Section: Introductionmentioning
confidence: 99%
“…Though significant efforts have been made to ensure security by the researchers and industry professionals, all the suggested steps are in the later stages of the development of a web application. This is one of the major flaws which render the web applications vulnerable and results in data breaches [3], [4]. The security estimation needs to be done at the initial stages of web application development.…”
Section: Introductionmentioning
confidence: 99%